Public opinion and public policy: the case of Kennedy and civil rights. - Stevens, Daniel (Presidential Studies Quarterly, 2002)
This article pits the current competing perspectives on the causal connection between presidential policy making and public opinion—that politicians are sensitive and responsive to movements in global public opinion, or public mood, over a range of issues as opposed to context- and issue-specific opinion—against each other in a case study of the Kennedy administration and civil rights policy. It finds that Kennedy's initial caution was the result of his greater attention to issue-specific opinion and that the subsequent change of strategy occurred as the salience and character of the civil rights question shifted. There is little evidence to suggest the administration was aware of, or responsive to, global public opinion. Reprinted by permission of the publisher.